Comparative study of ultrasonic-guided betamethasone local injection and extracorporeal shock wave therapy in post-stroke hemiplegic shoulder pain: a randomized clinical trial - Zhang, Jingjing; Mao, Huiwen; Gao, Fang; Li, Yan; Yang, Yang (Frontiers in Neurology, 2023)
Objective To compare the efficacy and safety of ultrasound-guided local injection (UGLI) of betamethasone around the shoulder and extracorporeal shock wave therapy(ESWT) in patients with hemiplegic shoulder pain . Method Forty-two patients with hemiplegic shoulder pain were randomly divided into UGLI group (N=21) and ESWT (N=21). In the UGLI group, betamethasone was injected at the pain point around the shoulder under ultrasonic localization. In the ESWT group, extracorporeal shock wave was performed at the pain points around the shoulder for 20min/ time, once a week, for 4 consecutive weeks. Both groups received rehabilitation training. Visual analogue scale (VAS) evaluation was performed at baseline, 1 hour ,1 week, and 1 month after treatment. Furthermore, Neer shoulder joint function scores, upper limb Fugl-Meyer assessment (FMA), Modified Barthel index (MBI), Hamilton Depression Scale (HAMD)，the MOS item short from health survey (SF-36) scores, and serum expression level of cytokine were evaluated at baseline and 1 month after treatment. Result After 1-hour treatment, the UGLI group showed greater effect in degree of pain than the ESWT group (P = 0.017);After 4 consecutive weeks intervention, the UGLI group showed significantly improvement on the level of cytokine expression in serum compared with the ESWT group (P < 0.05). The range of motion(ROM) of the hemiplegic shoulder (P < 0.05) has no difference between the two groups (P > 0.05). Conclusion The ultrasonic-guided betamethasone local injection and extracorporeal shock wave both can improve the hemiplegic shoulder pain. However, the UGLI can induce more cytokine expression level.